Numerical performances through artificial neural networks for solving the vector-borne disease with lifelong immunity - Akkilic, Ayse Nur; Sabir, Zulqurnain; Raja, Muhammad Asif Zahoor; Bulut, Hasan; Sadat, R.; Ali, Mohamed R. (Taylor & Francis Ltd, 2023)
The current study is related to solve a nonlinear vector-borne disease with a lifelong immunity model (VDLIM) by designing a computational stochastic framework using the strength of artificial Levenberg-Marquardt backpropagation neural network (ALMBNN). The detail of the nonlinear VDLIM is provided along with its five classes. The numerical performances of the results have been presented using the ALMBNN by taking three different cases to solve the nonlinear VDLIM using the training, sample data, testing and authentication. The selection of the statics is selected as 80% for training, while the data for both testing and validations is applied 10%. The results of the nonlinear VDLIM are performed using the ALMBNN and the correctness of the scheme is observed to compare the results with the reference solutions. The calculated performance of the results to solve the nonlinear VDLIM is applied for the reduction of the mean square error. In order to check the competence, efficacy, exactness and reliability of the ALMBNN, the numerical investigations using the proportional procedures based on the MSE, correlation, regression and error histograms are presented.
Keywords: Vector-borne disease with life immunity; nonlinear; Levenberg-Marquardt backpropagation; reference solutions; artificial neural network